Serum magnesium levels in patients of ischemic stroke and its correlation with neurological disability - Kotwal, Vishali; Maini, Rajesh (International Journal of Research in Medical Sciences, 2020)
Background: Stroke is a leading cause of death and disability worldwide acute ischaemic stroke accounts for 87% of strokes and mostly affects persons at the peak of their lives. Magnesium is known to have neuroprotective effects in ischemic stroke through a variety of mechanisms including decrease in glutamate release and inhibition of NMDA receptors and vasodilation. Previous studies on serum magnesium levels in stroke patients have shown variable results with many of them finding lower levels than in normal subjects. This study was undertaken to compare serum magnesium levels in patients of acute ischemic stroke with those of controls and also find a correlation if any between serum magnesium levels and neurological disability. Methods: This was a prospective non-interventional case-control study in which 50 patients of acute ischemic stroke in the age group of 20 to 80 years admitted in the department of Medicine Government Medical College Jammu from October 2019 to January 2020 were taken. Their serum magnesium levels were analysed within first 24 hours of admission and neurological disability was measured using modified Rankin Score. Serum magnesium levels were also estimated in 35 healthy controls for comparison. Results: Serum magnesium was lower in the study group (mean of 1.85±0.36) as compared to the control group (mean of 2.4±0.21) which was statistically significant (p value =0.001). Modified Rankin Score was 4 to 5 in 27 patients and 2 to 3 in 23 patients and it was negatively correlated with serum magnesium levels (r =-0.67). Conclusions: Ischemic stroke patients had lower serum magnesium levels as compared to healthy subjects in our study and also lower levels were seen in those with higher neurological disability.